A link between ghrelin and major depressive disorder: a mini review - Lis, Michał; Miłuch, Tymoteusz; Majdowski, Maciej; Zawodny, Tomasz (Frontiers in Psychiatry, 2024)
Ghrelin is primarily responsible for regulating energy balance as it increases appetite. However, in recent years its new physiological functions have been discovered -it regulates lipogenesis, plays a role in development of insulin resistance, and even acts protectively on heart muscle. Moreover, ghrelin was associated with many psychiatric disorders, including major depression disorder (MDD) or schizophrenia. Ghrelin levels were elevated in patients diagnosed with depression, and in patients after suicide attempt. Moreover, ghrelin was connected to depression among postmenopausal women, and was shown to be a predictive marker of MDD among elderly. Ghrelin may influence the mood disorders in various ways: by regulating stress response, inflammation, or altering neurotransmission in amygdala, dorsal raphe nucleus or hippocampus -brain regions previously connected to pathophysiology of MDD. Genetics variants of ghrelin and its receptor have also been associated with depression. Moreover, ghrelin can interfere with antidepressant's action and may play a role in treatment resistance. This review highlights the ghrelin's role in depression, summarizes the existing knowledge on the subject, and presents the ideas for further research.